2014
DOI: 10.1002/chem.201402783
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy for Storage and Transportation of Sensitive High‐Energy Materials: Guest‐Dependent Energy and Sensitivity of 3D Metal–Organic‐Framework‐Based Energetic Compounds

Abstract: Reaction of Co(II) with the nitrogen-rich ligand N,N-bis(1H-tetrazole-5-yl)-amine (H2bta) leads to a mixed-valence, 3D, porous, metal-organic framework (MOF)-based, energetic material with the nitrogen content of 51.78%, [Co9(bta)10(Hbta)2(H2O)10]n⋅(22 H2O)n (1). Compound 1 was thermohydrated to produce a new, stable, energetic material with the nitrogen content of 59.85% and heat of denotation of 4.537 kcal cm(-3), [Co9(bta)10(Hbta)2(H2O)10]n (2). Sensitivity tests show that 2 is more sensitivity to external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 61 publications
0
48
0
Order By: Relevance
“…According to experiment measurements and quantum chemical calculations, 1 is heat-resistant and has good energetic properties. Therefore, compared to the common explosive RDX (T dec = 483.2 K)[55] and energetic coordination compounds, such as CHP (T dec = 467.2 K) and NHP (T dec = 493.2 K)[56], 1 may be candidate as a thermally resistant energetic compound.Table 1. Crystal data and structure refinement for 1.…”
mentioning
confidence: 99%
“…According to experiment measurements and quantum chemical calculations, 1 is heat-resistant and has good energetic properties. Therefore, compared to the common explosive RDX (T dec = 483.2 K)[55] and energetic coordination compounds, such as CHP (T dec = 467.2 K) and NHP (T dec = 493.2 K)[56], 1 may be candidate as a thermally resistant energetic compound.Table 1. Crystal data and structure refinement for 1.…”
mentioning
confidence: 99%
“…Compound 1 was synthesized according to our recent work [11]. Compound 1 can be obtained by different routes under hydrothermal methods (Scheme 1).…”
Section: Synthesismentioning
confidence: 99%
“…Much recent research has focused on MOFs that contain nitrogen-rich heterocyclic ligands and non-toxic metal ions as newgeneration green primary explosives become a new concept for energetic materials [7][8][9][10]. In our recent work [11], we obtained two MOF-based energetic compounds that present an ingenious design for guest-dependent energy and sensitivity of 3D MOF-based energetic compound and also offer a practical strategy for the storage and transportation of high-energy materials.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many investigators have recently demonstrated the possibility of using nitrogen-rich MOFs as high explosives [25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. MOFs consist of metal ions (Pb 2+ , Ag + , etc.…”
Section: Introductionmentioning
confidence: 99%